Regulation (EU) No 1215/2012 as the European Union’s legal framework for the resolution of conflicts of competences and free movement of decisions in the field of the export of agri-food products - Serrano Martín, Jesús María (Przegląd Prawa Rolnego, 2018)
Regulation (EU) No 1215/2012 applies in civil and commercial matters, with the exception of criminal law, family law, insolvency law, succession law and other matters specified in that Regulation, such as social security or arbitration. Under the new law, the so-called exequatur procedure under Brussels I Regulation has been abolished. This means that a judicial decision issued in one of the EU Member States is recognised in other EU Member States without the need for a special procedure. If it is enforceable in the State in which the judgment was given, there is no need for a declaration of enforceability. There must be a link between the proceedings falling within the scope of this Regulation and the territory of EU Member States. Common rules on jurisdiction should in principle apply when the defendant is domiciled in one of the EU Member States. A defendant who is not domiciled in any of the EU Member States (whose habitual residence is outside the EU) should in principle be subject to the national rules of jurisdiction applicable in the territory of the EU Member State where the action has been brought. However, irrespective of the defendant’s residence, certain rules on jurisdiction apply in order to ensure the protection of consumers and workers, and to protect the jurisdiction of EU courts in situations where they have exclusive jurisdiction (e.g. in the case of real estate), and to respect the autonomy of the parties. The author addressed these issues to trade in agri-food products in the European Union.